Beyond Skin-Deep: The Relationship between Beauty Ideals and Identity Crisis in Scott Westerfeld's Uglies (Journal of the College of Languages (JCL), 2023)
Uglies (2005) is the first in Scott Westerfeld's Uglies series of novels. It is a science fiction literary work with a futuristic scenario that depicts a dystopian world in which people are preoccupied with unnatural standards of beauty. This novel essentially examines  the themes of beauty, identity and brainwashing. It also generates a debate regarding the damaging practices of cosmetic surgery. Adopting Erik Erikson's identity development theory and Henri Tajfel and John Turner's social identity theory as theoretical frameworks, this paper presents an analysis of how the pursuit of beauty ideals contributes to the formation of an externally appealing but inwardly conflicted self-image.Received on 22/2/2023  Accepted on 15/5/2023  Published on 1/6/2023